Construction of an overhead volley pass test for Filipino high school girls - Cuadra, Wilda Jayco 1948- (1978)
The total number of subjects involved in the collection of data was 150 high school girls of Jose Abad Santos High School in Binondo, Manila. The Cuadra Overhead Volley Pass test was validated using the French Cooper Repeated Wall Volley Test and the judges' ratings. The reliability coefficient provides evidence that the experimental test is consistent and meets the standards as established for sports skill testing. The test appeared to be an objective measure of volleyball passing ability for girls of high school age.
Vita.
Thesis (M.A.T. Physical Education)--University of the Philippines, Diliman.
Keywords: Volleyball for girls -- Philippines -- Binondo (Manila); High school seniors -- Philippines -- Binondo (Manila)